CULTURAL REPRESENTATION OF URBAN LIFESTYLE IN GOJEK’S ‘GOCAR LUXE’ ADVERTISEMENT (2023) - Lestari, Siti Khodijah; Nurhayani Saragih (International Journal of Cultural and Social Science, 2025)
The rise of digital technologies has reshaped urban mobility and consumption patterns, with app-based transport services such as Gojek functioning not only as practical solutions but also as cultural symbols for the urban middle and upper classes. This study employs Roland Barthes’s semiotic framework to examine how the GoCar Luxe (2023) advertisement constructs an urban lifestyle narrative through visual and verbal signs. Using a qualitative descriptive approach, the analysis identifies denotative, connotative, and mythical meanings embedded in the advertisement. The findings reveal that symbolic representations reinforce values of comfort, exclusivity, and efficiency as central to contemporary urban discourse. By unpacking these semiotic layers, the study highlights how digital advertising mediates cultural identity and legitimizes lifestyle aspirations, offering insights for communication and advertising studies on the interplay between media texts, cultural representation, and urban consumer values.